Os deutsch-brasilianer em oposição ao PRR : um estudo de caso a respeito dos municípios de origem germânica que derrotaram o PRR nas eleições de 1891 - Mossmann Sobrinho, Paulo Gilberto (2015)
This work has as its main theme the assessment of the Teutons in the political constitution of Rio Grande do Sul during the political transition period between the monarchy and the Republic. The work defines the period for analysis of facts to the 80s of 19th Century (which is possible to see the presence of the Teutons in Brazilian politics), taking as the critical point the year 1891, year of the constitutional election in Rio Grande do Sul. The results of the polls showed the opposition political character of German immigration areas. There will not be portrayed in this research the moments of great significance of the Federalist Revolution (1893-95), as they are considered a significant event which deserves a focused work especially on this historical fact. The research will be responding how the role of Deutsch-Brasilianer represented not only a mere spectator bias or adjuvant, but a decisive active actor role in the formation of situations of major political clashes policies, even to the point of to challenge the party hegemonic project established by the Republican Party Riograndense – PRR of Julio de Castilhos. Through a case study, the following question will be answered: how three municipalities newly emancipated (São Lourenço do Sul, Santa Cruz do Sul and Taquara do Mundo Novo), out of regions of large resorts (which was the solidified basis opposition to PRR, headed by Gaspar Silveira Martins), a solid presence in society Deutsch-Brasilianer, generated a strong focus of opposition to PRR – a strong opposition to point to defeat the PRR’s electoral machine, characterized by fraudulent elections at the election of the Constituent Assembly of Rio Grande do Sul, in 1891.